La pizarra digital interactiva como herramienta didáctica en el proceso de enseñanza de la lecto-escritura en los estudiantes con síndrome de Down leve del nivel básico - Chora Guamán, Carmita Doraliza (2018)
The research presented arises from the need to guide the use of interactive whiteboard (PDI), as a teaching tool, in the process of teaching reading and writing, in students with mild Down syndrome of the basic level, in the Santa Mariana de Jesus Educational Unit. For this, a pedagogical strategy aimed at teachers is proposed, which is modeled after the theoretical study carried out and the determination of the needs around the use of the PDI……….